The target therapeutic effect of functionalized graphene oxide nanoparticles graphene oxide–polyethylene glycol–folic acid-1–pyrenemethylamine hydrochloride-mediated RNA interference of HIF-1α gene in human pancreatic cancer cells. (August 2019) - Wan, Renming; Luan, Yufen; Wu, Zhouquan; Deng, Shengming; Peng, Mingya; Xu, Longbao; Wu, Yiwei; Qin, Xihu; Fan, Guanglei
The folate receptor-targeted graphene oxide gene transfection nanoparticles (graphene oxide–polyethylene glycol–folic acid-1–pyrenemethylamine hydrochloride) were prepared and used to deliver RNAi that specifically target the HIF-1α expression in pancreatic cancer Patu8988 cells. The gene expressions of HIF-1α and glucose transporter-1 (Glut-1) were determined by Western blot and reverse transcription PCR (RT-PCR). The transwell invasion chamber method was used to determine the invasive ability of Patu8988 cells, and 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay was used to determine the proliferation of Patu8988 cells before and after transfection. The cell cycle of Patu8988 and apoptosis were detected by flow cytometry, and the in vivo efficacy of graphene oxide–polyethylene glycol–folic acid-1–pyrenemethylamine hydrochloride/RNAi-HIF-1α particles was assessed in a nude mouse tumor model. The mRNA and protein levels of HIF-1α in cells transfected with functionalized particles were decreased under the hypoxia or normoxia state. The MTT assay showed that the cell growth of particle-treated group was significantly lower than that of control ( P < 0.05). Moreover, the proportion of G0/G1 cells in graphene oxide–polyethylene glycol–folic acid-1–pyrenemethylamine hydrochloride/RNAi-HIF-1α treated group was higher than that of control group ( P < 0.05). The number of migrated cells in the treated group was much lower than that in the control group ( P < 0.05). The data of this study indicated that gene silencing of HIF-1α inhibited the growth, proliferation, invasion, and metastasis of Patu8988 pancreatic cancer cells and reduced the mRNA expression of Glut-1 and 18 F- fluorodeoxyglucose ( 18 F-FDG) uptake in the pancreatic cancer cells, thereby accelerating the apoptosis of tumor cells and increasing the survival rate of animals. Under normoxic/hypoxic conditions, RNA interference for HIF-1α significantly decreased Glut-1 mRNA expression and uptake of 18 F-FDG in pancreatic cancer cells. Therefore, it is potentially feasible to use 18 F-FDG imaging for early assessing the therapeutic effect of graphene oxide–polyethylene glycol–folic acid-1–pyrenemethylamine hydrochloride on pancreatic cancer. The folate receptor-targeted graphene oxide gene transfection nanoparticles can be used to suppress tumor growth by specifically delivering into the tumor cells.